Complete Clinical and Trichoscopic Remission of Refractory Patch Alopecia Areata with a Multi-Modal Microneedling and Vitamin D3 Protocol: A Case Report - Stephanie Lukita; Ferra Olivia Mawu; Thigita Aga Pandaleke (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Refractory patch alopecia areata (AA) presents a significant therapeutic challenge, as many patients fail first-line treatments. This gap necessitates the exploration of novel, mechanistically-targeted therapeutic strategies. Case presentation: We present the case of a 44-year-old female with a 2.5 × 3.0 cm patch of AA, refractory to a 3-month compliant trial of topical 0.25% desoximetasone and 5% minoxidil. Baseline diagnostics included histopathology (peribulbar lymphocytic infiltrate), quantitative trichoscopy (yellow dots, black dots, exclamation mark hairs), and laboratory workup, which revealed a serum 25-hydroxyvitamin D [25(OH)D] insufficiency (18.2 ng/mL). A multi-modal protocol was initiated: (1) systemic 5,000 IU/day oral cholecalciferol, (2) 10 sessions of 1.5 mm microneedling at two-week intervals, and (3) immediate post-procedure application of topical 100,000 IU cholecalciferol. Significant regrowth of pigmented terminal hairs was observed by week 12. After 20 weeks (10 sessions), complete clinical regrowth was achieved. Final quantitative trichoscopy confirmed the full resolution of all pathological markers, with a healthy density of terminal hairs. The patient’s systemic 25(OH)D level was corrected to 41.5 ng/mL. The treatment was well-tolerated. Conclusion: This case report documents a complete remission associated with a multi-modal protocol. The contribution of the systemic vitamin D repletion is a major, unresolvable confounder, making attribution impossible. However, this hypothesis-generating case suggests a combined (systemic, physical, and topical) approach may represent a potential rescue strategy for refractory patch AA, warranting further controlled investigation.